2004
DOI: 10.1111/j.1460-9568.2004.03293.x
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent effects of CB1 cannabinoid gene disruption on anxiety‐like and social behaviour in mice

Abstract: Contrasting data were reported regarding the effects of cannabinoids on anxiety and social behaviour in both animals and humans. The cognitive effects of cannabinoids and their interactions with the HPA-axis raise the possibility that cannabinoid effects are context but not behaviour specific. To assess this hypothesis, we submitted CB1 receptor knock-out (CB1-KO) and wild-type (WT) mice to tests, which involved similar behaviours, but the behavioural context was different. The elevated plus-maze test was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
206
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(229 citation statements)
references
References 49 publications
17
206
4
2
Order By: Relevance
“…Specifically, we demonstrate that systemic administration of rimonabant precipitates anxiety-like behavior and more potently induces anorexia and weight loss in rats during early protracted withdrawal from a palatable high-sucrose diet compared with chow-fed controls. In addition, at a time when diet-cycled rats no longer showed the increased spontaneous anxiety-like behavior elicited by acute withdrawal from this diet (Cottone et al, 2009a;Cottone et al, 2009b), they still exhibited increased vulnerability to the anxiogenic-like effects of rimonabant (Haller et al, 2004). These results are consistent with the hypothesis that rats withdrawn from chronic, palatable diet cycling become vulnerable to the pharmacological effects of rimonabant.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Specifically, we demonstrate that systemic administration of rimonabant precipitates anxiety-like behavior and more potently induces anorexia and weight loss in rats during early protracted withdrawal from a palatable high-sucrose diet compared with chow-fed controls. In addition, at a time when diet-cycled rats no longer showed the increased spontaneous anxiety-like behavior elicited by acute withdrawal from this diet (Cottone et al, 2009a;Cottone et al, 2009b), they still exhibited increased vulnerability to the anxiogenic-like effects of rimonabant (Haller et al, 2004). These results are consistent with the hypothesis that rats withdrawn from chronic, palatable diet cycling become vulnerable to the pharmacological effects of rimonabant.…”
Section: Discussionsupporting
confidence: 80%
“…Symbols denote: *significant difference from Chow/Chow group po0.05, **po0.01. Haller et al, 2004). In addition, rimonabant-precipitated anxiety-like behavior in rats withdrawn from chronic, intermittent access to palatable food was independent of the degree of adrenocortical activation.…”
Section: Discussionmentioning
confidence: 83%
“…In support of this hypothesis, it has been demonstrated that endocannabinoids modulate hypothalamus-pituitaryadrenal axis function (Haller et al, 2004;Manzanares et al, 1999;Patel et al, 2004). In particular, earlier studies from our laboratory (Patel et al, 2004) demonstrated that CB 1 receptor blockade potentiates restraint stress-induced hypothalamus-pituitary-adrenal axis activation and neuronal activity in the paraventricular nucleus of the hypothalamus, and CB 1 receptor activation blocks restraint stress-induced hypothalamus-pituitary-adrenal axis activation.…”
Section: Discussionmentioning
confidence: 55%
“…For example, blockade of endogenous CB 1 receptor activity with rimonabant increases adrenocorticotropin hormone and corticosterone plasma concentrations (Manzanares et al, 1999). Similarly, basal adrenocorticotropin hormone concentrations are increased in CB 1 receptor null mice (Haller et al, 2004). On the other hand, inhibition of fatty acid amide hydrolase (FAAH) activity during stress inhibits activation of the hypothalamic-pituitaryadrenal axis (Patel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…17 These discrepancies might be ascribed to differences in the genetic background of the rodent 8,15,16 or in the test conditions, 18 especially regarding the averseness of the test situation. 19 Given the high comorbidity between anxiety and major depression, 20 recent research has also focused on a potential role of the endocannabinoid system in the pathology of major depression 13,21 particularly of the melancholic subtype. 13 CB1 receptor-deficient mice share several symptoms with patients suffering from melancholic depression such as, for example, altered responsiveness to reward stimuli, 22 altered neurovegetative functions, 23 a predominance and persistence of aversive memories, 8,9 and possibly neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%